PENGARUH BUDAYA ORGANISASI TERHADAP KINERJA GURU DI SMK NEGERI 2 NGAWI TAHUN 2014 - Anna Tri Yuliastuti Wulandari (EQUILIBRIUM : Jurnal Ilmiah Ekonomi dan Pembelajarannya, 2016)
This research have a purpose to know organizational culture in SMK Neger 2 Ngawi Year 2014, to know performance learn SMK Country 2 Ngawi Year 2014 and to know is there any cultural influence of organization to performance learn SMK Country 2 Ngawi Year 2014. Determination of sampel in this research use saturated sampel that is all teacher in SMK Country 2 Ngawi Year 2014 amounting to 40 teacher. Data collecting use or enquette of kuisioner. In analysing data use statistical aid method and use linear analysis modestly to test hypothesis which is told in research. Pursuant to result of research obtained by the level of value of rhitung is 0,834 and rtabel 0,312, on the other hand the level of Sighitung 0,000. and Sigprob 0,05. Matter this means that value of rhitung ≥ rtabel ( 0,834 ≥ 0,312) or Sighitung ≤ Sigprob ( 0,000 ≤ 0,05). On the basis of correlation test, test F and test of t can be concluded that there is influence among/between Organizational Culture to Performance Learn In SMK Country 2 Ngawi Year 2014.